Changes in gymnasts motor abilities during the nine month training process of female gymnasts 5-6 years of age - Zivcic-Markovic, K.; Cavar, I.; Sporis, G. (Science of Gymnastics Journal, 2012)
This study was aimed to determine changes in the development of some motor abilities of female gymnasts aged 5-6 years during the nine-month training process. Six gymnasts, members of gymnasts club "Novi Zagreb"from Zagreb aged from 5 - 6 years, volunteered in this study. They were involved in the training process, which was consistent of the elements of "B" (higher level) program for girls, for nine months. Changes in motor variables were recorded in the 7 time points for each subject. One way ANOVA for repeated measures determined if changes in measured motor abilities would appear through nine month training process. The primarily finding of this study supported our research hypothesis, with statistically significant improvement in all of measured motor abilities (power and flexibility), except in explosive power.